A 55-Kilodalton Immunodominant Antigen of Porphyromonas gingivalis W50 Has Arisen via Horizontal Gene Transfer - Hanley, Shirley A. (American Society for Microbiology (ASM), 1999)
A 55-kDa outer membrane protein of Porphyromonas gingivalis W50 is a significant target of the serum immunoglobulin G antibody response of periodontal disease patients and hence may play an important role in host-bacterium interactions in periodontal disease. The gene encoding the 55-kDa antigen (ragB, for receptor antigen B) was isolated on a 9.5-kb partial Sau3AI fragment of P. gingivalis W50 chromosomal DNA in pUC18 by immunoscreening with a monoclonal antibody to this antigen. The 1.6-kb open reading frame (ORF) encoding RagB was located via subcloning and nested-deletion analysis. Sequence analysis demonstrated the presence of an upstream 3.1-kb ORF (ragA) which is cotranscribed with ragB. A number of genetic characteristics suggest that the ragAB locus was acquired by a horizontal gene transfer event. These include a significantly reduced G+C content relative to that of the P. gingivalis chromosome (42 versus 48%) and the presence of mobility elements flanking this locus in P. gingivalis W50. Furthermore, Southern blotting and PCR analyses showed a restricted distribution of this locus in laboratory and clinical isolates of this bacterium. The association of ragAB(+) P. gingivalis with clinical status was examined by PCR analysis of subgingival samples. ragAB(+) was not detected in P. gingivalis-positive shallow pockets from periodontal disease patients but was present in 36% of the P. gingivalis-positive samples from deep pockets. These data suggest that the ragAB locus was acquired by certain P. gingivalis strains via horizontal gene transfer and that the acquisition of this locus may facilitate the survival of these strains at sites of periodontal destruction.